A method for improving the wear resistance of carbon-carbon composite materials by boron doping
Through boron doping technology and carbon nanotube modification, a stable mesh structure is formed, which solves the problem of insufficient wear resistance and corrosion resistance of carbon-carbon composite materials, significantly improves the strength and stability of the material, and is suitable for complex work environment.
Patent Information
- Application Number
- CN202411320432.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-23
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon-carbon composite materials, and particularly relates to a method for improving the wear resistance of a carbon-carbon composite material by boron doping. Background Art
[0002] Carbon-carbon composites refer to a type of composite material that uses carbon fiber as reinforcement and carbon as the matrix. Carbon-carbon composites are widely used in aerospace, automotive, electronics and other fields due to their excellent high-temperature stability, good mechanical properties and low thermal expansion coefficient.
[0003] In order to meet the needs of long-term use in complex and harsh working environments, the wear resistance of carbon-carbon composite materials needs to be further improved.
[0004] CN116375489A discloses a carbon-carbon composite material and a preparation method thereof, specifically disclosing that carbon fibers are woven to obtain a carbon fiber woven body, and then placing it in a carbon source for chemical vapor infiltration treatment to obtain a carbon-carbon preform, and vacuum impregnating the carbon-carbon preform, wherein the impregnating agent is a polymer obtained by the reaction of ethylene tar and a hydrogenating agent, and after impregnation, carbonization treatment and high-temperature treatment are performed to obtain a carbon-carbon composite material;
[0005] The carbon-carbon composite material prepared by this method has high density and hardness and is wear-resistant, but its wear resistance is still at a low level and its corrosion resistance is poor.
[0006] During the research and development process, the applicant also found that boron, as an effective dopant, can significantly improve the wear resistance of the material, but it has not been fully studied and optimized in the preparation process of carbon-carbon composite materials.
[0007] Therefore, providing a method for preparing a carbon-carbon composite material, improving the wear resistance of the material by boron doping, and ensuring that the material has good corrosion resistance are technical problems that need to be urgently solved in the prior art. Summary of the invention
[0008] In order to solve the technical problems existing in the prior art, the present invention provides a method for improving the wear resistance of carbon-carbon composite materials by boron doping, and the prepared material has good wear resistance and corrosion resistance.
[0009] In view of the above technical problems, the present invention adopts the following technical solutions:
[0010] A method for improving the wear resistance of a carbon-carbon composite material by boron doping includes preparing a hydrolyzed carbon-boron precursor, preparing a modified carbon nanotube, preparing an impregnation liquid matrix, preparing an impregnation liquid, impregnating, carbonizing, and densifying. The specific operations are as follows:
[0011] 1. Preparation of Hydrolyzed Carbon-Boron Precursor
[0012] (1) Boron doping
[0013] Add polyacrylonitrile to N,N-dimethylformamide, stir evenly, add boric acid, and perform ultrasonic treatment. The ultrasonic time is 30-35 minutes, the ultrasonic power is 342-357W, and the ultrasonic frequency is 93-100kHz. After the ultrasonic treatment, place it at 156-160°C for heat treatment. The heat treatment time is 1.2-1.5 hours. After the heat treatment, naturally cool to room temperature to obtain a carbon-boron precursor.
[0014] The mass ratio of N,N-dimethylformamide, polyacrylonitrile and boric acid is 28-32:9-11:0.47-0.53;
[0015] (2) Hydrolysis
[0016] The carbon-boron precursor is placed in a sodium hydroxide solution, the temperature is increased to 92-97° C., and the reaction is stirred at 200-215 rpm for 1.8-2.2 hours. After the stirring reaction is completed, the solution is washed and dried to obtain a hydrolyzed carbon-boron precursor;
[0017] The mass concentration of the sodium hydroxide solution is 20-25%;
[0018] The mass ratio of the carbon-boron precursor to the sodium hydroxide solution is 8.2-8.6:34-36.
[0019] 2. Preparation of modified carbon nanotubes
[0020] (1) Preprocessing
[0021] The carbon nanotubes are placed in a sealed container, deionized water and sodium dodecyl sulfate are added and stirred, dihydroxymethylbutyric acid and tartaric acid are added after stirring, the temperature is raised to 83-89° C., stirring is performed, the stirring speed is 547-572 rpm, the stirring time is 22-30 min, after the stirring is completed, the mixture is filtered and washed, and dried at 76-80° C. for 2.8-3.3 h to obtain carboxylated carbon nanotubes;
[0022] The mass ratio of the carbon nanotubes, deionized water, sodium dodecyl sulfate, dihydroxymethylbutyric acid and tartaric acid is 11.0-11.4:92-100:0.8-1.0:1.1-1.5:1.4-1.7;
[0023] (2) Modification
[0024] The carboxylated carbon nanotubes are placed in a sealed container, thionyl chloride is added, the temperature is raised to 108-113°C for stirring reaction, the reaction time is 18-22 hours, after the reaction is completed, the carbon nanotubes are filtered and dried to obtain acyl chloride; the carbon nanotubes are added to toluene, the mixture is stirred evenly, triethylamine and dopamine are added, the mixture is stirred evenly, the temperature is raised to 100-105°C, the reaction is refluxed for 5.8-6.3 hours, and after the reaction is completed, the modified carbon nanotubes are obtained;
[0025] The mass volume ratio of the carboxylated carbon nanotubes and thionyl chloride is 7.8-8.2 g:740-760 mL;
[0026] The mass volume ratio of the toluene, acyl chloride carbon nanotubes, triethylamine and dopamine is 340-360 mL: 2.8-3.2 g: 0.6-0.8 g: 0.4-0.6 g.
[0027] 3. Preparation of impregnation liquid matrix
[0028] The hydrolyzed carbon-boron precursor is placed in dimethyl sulfoxide, and the modified carbon nanotubes are added after being stirred evenly, and homogenized for 5-7 minutes at a homogenization pressure of 4.0-4.5 MPa. After the homogenization is completed, the temperature is increased to 76-80° C., and the reaction is carried out in a nitrogen atmosphere for 5.3-5.7 hours. After the reaction is completed, the reaction is naturally cooled to room temperature, filtered, washed, and dried to obtain an impregnation liquid matrix;
[0029] The mass volume ratio of the hydrolyzed carbon-boron precursor, dimethyl sulfoxide and modified carbon nanotubes is 8.3-8.7 g: 215-225 mL: 2.0-2.2 g.
[0030] 4. Preparation of Impregnation Solution
[0031] The impregnation liquid matrix is mixed with the ethanol solution, and ultrasonic treatment is performed, the ultrasonic time is 20-30 minutes, the ultrasonic power is 252-265W, and the ultrasonic frequency is 35-40kHz. After the ultrasonic treatment, N-(2-hydroxyethyl)ethylenediamine-N,N',N'-triacetic acid and palmitic acid are added, and the mixture is stirred at a temperature of 58-62°C and a stirring time of 30-40 minutes. After the stirring is completed, an impregnation liquid is obtained;
[0032] The mass concentration of the ethanol solution is 27-33%;
[0033] The mass volume ratio of the impregnation liquid matrix, the ethanol solution, N-(2-hydroxyethyl)ethylenediamine-N,N',N'-triacetic acid and palmitic acid is 25.4-26.0 g: 48-52 mL: 0.8-1.2 g: 1.2-1.4 g.
[0034] 5. Impregnation
[0035] The carbon fibers are placed in a sealed container, an impregnation liquid is introduced, the temperature is raised to 204-208°C, and the impregnation is carried out at 204-208°C for 37-43 minutes. After the impregnation, argon gas is introduced, the temperature is controlled at 204-208°C, the pressure is raised to 3.0-3.5MPa, and the temperature and pressure are maintained for 2.7-3.3 hours. After the temperature and pressure are maintained, a primary impregnated body is obtained;
[0036] The density of the carbon fiber cloth is 0.52-0.58 g / cm 3 , woven from 12K long fibers;
[0037] The mass ratio of the carbon fiber cloth to the impregnating liquid is 1:3.0-3.4.
[0038] 6. Carbonization
[0039] The primary impregnated body is placed in a carbonization furnace and carbonized under an argon atmosphere. The temperature is increased to 740-760°C at a rate of 7.8-8.2°C / min and kept warm for 35-45 minutes. After the insulation is completed, the temperature is increased to 1240-1300°C at a rate of 4.5-5.5°C / min and kept warm for 6.5-7.5 hours. After the insulation is completed, a primary carbon-carbon composite material is obtained.
[0040] 7. Densification
[0041] The primary carbon-carbon composite material is placed in a sealed container, an impregnation liquid is introduced, the temperature is increased to 208-212°C, and the impregnation is carried out at 208-212°C for 35-40 minutes. After the impregnation, argon is introduced, the temperature is controlled at 208-212°C, the pressure is increased to 3.8-4.2MPa, and the temperature and pressure are maintained for 3.3-3.7 hours. After the temperature and pressure are maintained, a secondary impregnation body is obtained; the secondary impregnation body is placed in a carbonization furnace in an argon atmosphere. Carbonization was carried out at 600-640°C at a rate of 6.0-7.0°C / min, and the temperature was kept for 25-35min. After the heat preservation, the temperature was increased to 1300-1340°C at a rate of 3.7-4.3°C / min, and the temperature was kept for 6.2-6.8h. After the heat preservation, the temperature was increased to 1860-1900°C at a rate of 3.0-3.5°C / min, and the temperature was kept for 2.2-2.8h to obtain a carbon-carbon composite material;
[0042] The mass ratio of the primary carbon-carbon composite material to the impregnation liquid is 1:3.7-4.3.
[0043] Compared with the prior art, the present invention has achieved the following beneficial effects:
[0044] 1. The present invention modifies carbon nanotubes by first using an organic acid to acidify the carbon nanotubes so that the surface of the carbon nanotubes contains more carboxyl groups, then performing an acyl chloride treatment, and then reacting with amino groups to complete the modification of the carbon nanotubes. The prepared modified carbon nanotubes have good dispersibility, and triethylamine and dopamine present a cross-linked stable structure on the surface of the carbon nanotubes, thereby enhancing the strength and stability of the carbon nanotubes. Polyacrylonitrile is used as a carbon source, and a composite of boric acid and polyacrylonitrile is used to make the matrix have better fluidity and increase the bonding strength of the interface. At the same time, boron can promote the carbon matrix graphite The degree of chemistry is increased, and after being hydrolyzed, it is combined with carbon nanotubes, and the two are cross-linked. The obtained impregnation liquid matrix presents a stable network structure. The combination of N-(2-hydroxyethyl)ethylenediamine-N,N',N'-triacetic acid and palmitic acid components makes the impregnation liquid have good homogeneity, good dispersibility, and excellent bonding performance. In addition, the impregnation liquid contains more hydroxyl, carboxyl, amino and other groups, which improves the compatibility with carbon fiber, thereby making the carbon fiber cloth fully and evenly compounded with the impregnation liquid. Under the joint action, the wear resistance and strength performance of the composite material are effectively enhanced, and the stability is improved;
[0045] 2. The carbon-carbon composite material prepared by the method of the present invention has good wear resistance, and the wear rate is (0.045-0.062)×10 -5 cm 3 N -1 m -1 ;
[0046] 3. The carbon-carbon composite material prepared by the method of the present invention has a compressive strength of 203.5-211.4 MPa, a flexural strength of 177.2-184.3 MPa, and a tensile strength of 129.1-136.0 MPa;
[0047] 4. The carbon-carbon composite material prepared by the method of the present invention has a mass loss rate of 0.10-0.14% after high-temperature treatment at 1000°C for 5.0h;
[0048] 5. The carbon-carbon composite material prepared by the method of the present invention was immersed in a 20wt% sodium chloride solution with a mass of 4 times, the immersion temperature was 40°C, the immersion time was 100 hours, and after the immersion, it was washed and dried, and then immersed in a 20wt% sodium carbonate solution with a mass of 4 times, the immersion temperature was 62°C, and the immersion time was 100 hours. After the immersion, after washing and drying, the compressive strength was measured to be 191.3-201.0MPa, the flexural strength was 168.7-177.5MPa, and the tensile strength was 121.7-129.9MPa. DETAILED DESCRIPTION
[0049] In order to more clearly understand the technical features, purposes and effects of the present invention, specific embodiments of the present invention are now described.
[0050] Example 1
[0051] 1. Preparation of Hydrolyzed Carbon-Boron Precursor
[0052] (1) Boron doping
[0053] Add 10 g of polyacrylonitrile to 30 g of N,N-dimethylformamide, stir evenly, add 0.5 g of boric acid, and perform ultrasonic treatment. The ultrasonic time is 32 min, the ultrasonic power is 350 W, and the ultrasonic frequency is 96 kHz. After the ultrasonic treatment, place it at 158 ° C for heat treatment. The heat treatment time is 1.3 h. After the heat treatment, it is naturally cooled to room temperature to obtain a carbon-boron precursor;
[0054] (2) Hydrolysis
[0055] 8.4 g of the carbon-boron precursor was placed in 35 g of a sodium hydroxide solution, the temperature was raised to 94° C., and the mixture was stirred at 210 rpm for 2.0 h. After the stirring reaction was completed, the mixture was washed and dried to obtain a hydrolyzed carbon-boron precursor.
[0056] The mass concentration of the sodium hydroxide solution is 23%.
[0057] 2. Preparation of modified carbon nanotubes
[0058] (1) Preprocessing
[0059] 11.2 g of carbon nanotubes were placed in a sealed container, 96 g of deionized water and 0.9 g of sodium dodecyl sulfate were added and stirred, and after stirring evenly, 1.3 g of dihydroxymethylbutyric acid and 1.6 g of tartaric acid were added, and the temperature was raised to 86° C. and stirred at a stirring speed of 560 rpm for 25 min. After the stirring was completed, the mixture was filtered and washed, and dried at 78° C. for 3.0 h to obtain carboxylated carbon nanotubes;
[0060] (2) Modification
[0061] 8.0g of carboxylated carbon nanotubes were placed in a sealed container, 750mL of dichlorothionyl was added, the temperature was raised to 110°C for stirring reaction, the reaction time was 20h, after the reaction was completed, it was filtered and dried to obtain chlorinated carbon nanotubes; 3.0g of chlorinated carbon nanotubes were added to 350mL of toluene, after stirring evenly, 0.7g of triethylamine and 0.5g of dopamine were added, after stirring evenly, the temperature was raised to 103°C, refluxed for 6.0h, after the reaction was completed, modified carbon nanotubes were obtained.
[0062] 3. Preparation of impregnation liquid matrix
[0063] 8.5 g of hydrolyzed carbon-boron precursor was placed in 220 mL of dimethyl sulfoxide, stirred evenly, and then 2.1 g of modified carbon nanotubes was added for homogenization. The homogenization time was 6 min and the homogenization pressure was 4.2 MPa. After the homogenization was completed, the temperature was raised to 78 ° C and the reaction was carried out under a nitrogen atmosphere for 5.5 h. After the reaction was completed, it was naturally cooled to room temperature. After filtering, washing and drying, the impregnation liquid matrix was obtained.
[0064] 4. Preparation of Impregnation Solution
[0065] 25.7 g of the impregnation liquid matrix was mixed with 50 mL of ethanol solution, and ultrasonic treatment was performed. The ultrasonic time was 25 min, the ultrasonic power was 260 W, and the ultrasonic frequency was 38 kHz. After the ultrasonic treatment, 1.0 g of N-(2-hydroxyethyl)ethylenediamine-N,N',N'-triacetic acid and 1.3 g of palmitic acid were added, and the mixture was stirred at 60° C. for 35 min. After the stirring was completed, an impregnation liquid was obtained.
[0066] The mass concentration of the ethanol solution is 30%.
[0067] 5. Impregnation
[0068] The carbon fibers were placed in a sealed container, impregnated with liquid, the temperature was raised to 206°C, and the mixture was impregnated at 206°C for 40 minutes. After the impregnation, argon was introduced, the temperature was controlled at 206°C, the pressure was raised to 3.3 MPa, and the mixture was kept at this temperature for 3.0 hours. After the impregnation, a primary impregnated body was obtained.
[0069] The density of the carbon fiber cloth is 0.55 g / cm 3 , woven from 12K long fibers;
[0070] The mass ratio of the carbon fiber cloth to the impregnating liquid is 1:3.2.
[0071] 6. Carbonization
[0072] The primary impregnated body is placed in a carbonization furnace and carbonized under an argon atmosphere. The temperature is increased to 750°C at a rate of 8.0°C / min and kept warm for 40 minutes. After the insulation, the temperature is increased to 1270°C at a rate of 5.0°C / min and kept warm for 7.0 hours. After the insulation, a primary carbon-carbon composite material is obtained.
[0073] 7. Densification
[0074] The primary carbon-carbon composite material is placed in a sealed container, an impregnation liquid is introduced, the temperature is increased to 210°C, and the mixture is impregnated at 208°C for 37 minutes. After the impregnation, argon is introduced, the temperature is controlled to be 210°C, the pressure is increased to 4.0MPa, and the mixture is kept at this temperature for 3.5 hours. After the heat preservation and pressure preservation are completed, a secondary impregnation body is obtained. The secondary impregnation body is placed in a carbonization furnace, carbonized in an argon atmosphere, and the temperature is increased to 620°C at a rate of 6.5°C / min, and the mixture is kept at this temperature for 30 minutes. After the heat preservation is completed, the temperature is increased to 1320°C at a rate of 4.0°C / min, and the mixture is kept at this temperature for 6.5 hours. After the heat preservation is completed, the temperature is increased to 1880°C at a rate of 3.2°C / min, and the mixture is kept at this temperature for 2.5 hours to obtain a carbon-carbon composite material.
[0075] The mass ratio of the primary carbon-carbon composite material to the impregnation liquid is 1:4.0.
[0076] Example 2
[0077] 1. Preparation of Hydrolyzed Carbon-Boron Precursor
[0078] (1) Boron doping
[0079] Add 9 g of polyacrylonitrile to 28 g of N,N-dimethylformamide, stir evenly, add 0.47 g of boric acid, and perform ultrasonic treatment. The ultrasonic time is 30 min, the ultrasonic power is 342 W, and the ultrasonic frequency is 93 kHz. After the ultrasonic treatment, place it at 156 ° C for heat treatment. The heat treatment time is 1.2 h. After the heat treatment, it is naturally cooled to room temperature to obtain a carbon-boron precursor;
[0080] (2) Hydrolysis
[0081] 8.2 g of the carbon-boron precursor was placed in 34 g of a sodium hydroxide solution, the temperature was raised to 92° C., and the mixture was stirred at 200 rpm for 1.8 h. After the stirring reaction was completed, the mixture was washed and dried to obtain a hydrolyzed carbon-boron precursor.
[0082] The mass concentration of the sodium hydroxide solution is 20%.
[0083] 2. Preparation of modified carbon nanotubes
[0084] (1) Preprocessing
[0085] 11.0 g of carbon nanotubes were placed in a sealed container, 92 g of deionized water and 0.8 g of sodium dodecyl sulfate were added and stirred, and after stirring evenly, 1.1 g of dihydroxymethylbutyric acid and 1.4 g of tartaric acid were added, and the temperature was raised to 83 ° C, and stirred at a stirring speed of 547 rpm for 22 min. After the stirring was completed, the mixture was filtered and washed, and dried at 76 ° C for 3.3 h to obtain carboxylated carbon nanotubes;
[0086] (2) Modification
[0087] 7.8g of carboxylated carbon nanotubes were placed in a sealed container, 740mL of dichlorothionyl was added, the temperature was raised to 108°C for stirring reaction, the reaction time was 18h, after the reaction was completed, it was filtered and dried to obtain chlorinated carbon nanotubes; 2.8g of chlorinated carbon nanotubes were added to 340mL of toluene, after stirring evenly, 0.6g of triethylamine and 0.4g of dopamine were added, after stirring evenly, the temperature was raised to 100°C, and refluxed for 5.8h. After the reaction was completed, modified carbon nanotubes were obtained.
[0088] 3. Preparation of impregnation liquid matrix
[0089] 8.3 g of hydrolyzed carbon-boron precursor was placed in 215 mL of dimethyl sulfoxide, stirred evenly, and then 2.0 g of modified carbon nanotubes were added for homogenization. The homogenization time was 5 min and the homogenization pressure was 4.0 MPa. After the homogenization was completed, the temperature was increased to 76 ° C and the reaction was carried out under a nitrogen atmosphere for 5.3 h. After the reaction was completed, it was naturally cooled to room temperature. After filtering, washing and drying, the impregnation liquid matrix was obtained.
[0090] 4. Preparation of Impregnation Solution
[0091] 25.4 g of the impregnation liquid matrix was mixed with 48 mL of ethanol solution, and ultrasonic treatment was performed. The ultrasonic time was 20 min, the ultrasonic power was 252 W, and the ultrasonic frequency was 35 kHz. After the ultrasonic treatment, 0.8 g of N-(2-hydroxyethyl)ethylenediamine-N,N',N'-triacetic acid and 1.4 g of palmitic acid were added, and the mixture was stirred at 58 ° C. The stirring time was 30 min. After the stirring was completed, an impregnation liquid was obtained.
[0092] The mass concentration of the ethanol solution is 27%.
[0093] 5. Impregnation
[0094] The carbon fibers were placed in a sealed container, impregnated with liquid, the temperature was raised to 204°C, and the mixture was impregnated at 204°C for 37 minutes. After the impregnation, argon was introduced, the temperature was controlled at 204°C, the pressure was raised to 3.0 MPa, and the mixture was kept at this temperature for 2.7 hours. After the impregnation, a primary impregnated body was obtained.
[0095] The density of the carbon fiber cloth is 0.52 g / cm 3 , woven from 12K long fibers;
[0096] The mass ratio of the carbon fiber cloth to the impregnating liquid is 1:3.0.
[0097] 6. Carbonization
[0098] The primary impregnated body is placed in a carbonization furnace and carbonized under an argon atmosphere. The temperature is increased to 740°C at a rate of 7.8°C / min and kept warm for 35 minutes. After the insulation, the temperature is increased to 1240°C at a rate of 4.5°C / min and kept warm for 7.5 hours. After the insulation, a primary carbon-carbon composite material is obtained.
[0099] 7. Densification
[0100] The primary carbon-carbon composite material is placed in a sealed container, an impregnation liquid is introduced, the temperature is increased to 208°C, and the mixture is impregnated at 208°C for 35 minutes. After the impregnation, argon is introduced, the temperature is controlled to be 208°C, the pressure is increased to 3.8MPa, and the mixture is kept at this temperature for 3.3 hours. After the heat preservation and pressure preservation are completed, a secondary impregnation body is obtained. The secondary impregnation body is placed in a carbonization furnace, and carbonized in an argon atmosphere, and the temperature is increased to 600°C at a rate of 6.0°C / min, and the mixture is kept at this temperature for 25 minutes. After the heat preservation is completed, the temperature is increased to 1300°C at a rate of 3.7°C / min, and the mixture is kept at this temperature for 6.2 hours. After the heat preservation is completed, the temperature is increased to 1860°C at a rate of 3.0°C / min, and the mixture is kept at this temperature for 2.2 hours to obtain a carbon-carbon composite material.
[0101] The mass ratio of the primary carbon-carbon composite material to the impregnation liquid is 1:3.7.
[0102] Example 3
[0103] 1. Preparation of Hydrolyzed Carbon-Boron Precursor
[0104] (1) Boron doping
[0105] Add 11 g of polyacrylonitrile to 32 g of N,N-dimethylformamide, stir evenly, add 0.53 g of boric acid, and perform ultrasonic treatment. The ultrasonic time is 35 min, the ultrasonic power is 357 W, and the ultrasonic frequency is 100 kHz. After the ultrasonic treatment, place it at 160 ° C for heat treatment. The heat treatment time is 1.5 h. After the heat treatment, it is naturally cooled to room temperature to obtain a carbon-boron precursor;
[0106] (2) Hydrolysis
[0107] 8.6 g of the carbon-boron precursor was placed in 36 g of a sodium hydroxide solution, the temperature was raised to 97° C., and the mixture was stirred at 215 rpm for 2.2 h. After the stirring reaction was completed, the mixture was washed and dried to obtain a hydrolyzed carbon-boron precursor.
[0108] The mass concentration of the sodium hydroxide solution is 25%.
[0109] 2. Preparation of modified carbon nanotubes
[0110] (1) Preprocessing
[0111] 11.4 g of carbon nanotubes were placed in a sealed container, 100 g of deionized water and 1.0 g of sodium dodecyl sulfate were added and stirred, and after stirring evenly, 1.5 g of dihydroxymethylbutyric acid and 1.7 g of tartaric acid were added, and the temperature was raised to 89° C. and stirred at a stirring speed of 572 rpm for 30 min. After the stirring was completed, the mixture was filtered and washed, and dried at 80° C. for 2.8 h to obtain carboxylated carbon nanotubes;
[0112] (2) Modification
[0113] 8.2g of carboxylated carbon nanotubes were placed in a sealed container, 760mL of dichlorothionyl was added, the temperature was raised to 113°C for stirring reaction, the reaction time was 22h, after the reaction was completed, it was filtered and dried to obtain chlorinated carbon nanotubes; 3.2g of chlorinated carbon nanotubes were added to 360mL of toluene, after stirring evenly, 0.8g of triethylamine and 0.6g of dopamine were added, after stirring evenly, the temperature was raised to 105°C, refluxed for 6.3h, after the reaction was completed, modified carbon nanotubes were obtained.
[0114] 3. Preparation of impregnation liquid matrix
[0115] 8.7 g of hydrolyzed carbon-boron precursor was placed in 225 mL of dimethyl sulfoxide, stirred evenly, and then 2.2 g of modified carbon nanotubes were added for homogenization. The homogenization time was 7 min and the homogenization pressure was 4.5 MPa. After the homogenization was completed, the temperature was increased to 80 ° C and the reaction was carried out under a nitrogen atmosphere for 5.7 h. After the reaction was completed, it was naturally cooled to room temperature. After filtering, washing and drying, the impregnation liquid matrix was obtained.
[0116] 4. Preparation of Impregnation Solution
[0117] 26.0 g of the impregnation liquid matrix was mixed with 52 mL of ethanol solution, and ultrasonic treatment was performed. The ultrasonic time was 30 min, the ultrasonic power was 265 W, and the ultrasonic frequency was 40 kHz. After the ultrasonic treatment, 1.2 g of N-(2-hydroxyethyl)ethylenediamine-N,N',N'-triacetic acid and 1.2 g of palmitic acid were added, and the mixture was stirred at 62 ° C. The stirring time was 40 min. After the stirring was completed, an impregnation liquid was obtained.
[0118] The mass concentration of the ethanol solution is 33%.
[0119] 5. Impregnation
[0120] The carbon fibers were placed in a sealed container, impregnated with liquid, the temperature was raised to 208°C, and the mixture was impregnated at 208°C for 43 minutes. After the impregnation, argon was introduced, the temperature was controlled at 208°C, the pressure was raised to 3.5 MPa, and the mixture was kept at this temperature for 3.3 hours. After the impregnation, a primary impregnated body was obtained.
[0121] The density of the carbon fiber cloth is 0.58 g / cm 3 , woven from 12K long fibers;
[0122] The mass ratio of the carbon fiber cloth to the impregnating liquid is 1:3.4.
[0123] 6. Carbonization
[0124] The primary impregnated body was placed in a carbonization furnace and carbonized under an argon atmosphere. The temperature was raised to 760°C at a rate of 8.2°C / min and kept warm for 45 minutes. After the insulation, the temperature was raised to 1300°C at a rate of 5.5°C / min and kept warm for 6.5 hours. After the insulation, a primary carbon-carbon composite material was obtained.
[0125] 7. Densification
[0126] The primary carbon-carbon composite material is placed in a sealed container, an impregnation liquid is introduced, the temperature is increased to 212°C, and the mixture is impregnated at 212°C for 40 minutes. After the impregnation, argon is introduced, the temperature is controlled to be 212°C, the pressure is increased to 3.4MPa, and the mixture is kept at this temperature for 3.7 hours. After the heat preservation and pressure preservation are completed, a secondary impregnation body is obtained. The secondary impregnation body is placed in a carbonization furnace, carbonized in an argon atmosphere, and the temperature is increased to 640°C at a rate of 7.0°C / min, and the mixture is kept at this temperature for 35 minutes. After the heat preservation is completed, the temperature is increased to 1340°C at a rate of 4.3°C / min, and the mixture is kept at this temperature for 6.8 hours. After the heat preservation is completed, the temperature is increased to 1900°C at a rate of 3.5°C / min, and the mixture is kept at this temperature for 2.8 hours to obtain a carbon-carbon composite material.
[0127] The mass ratio of the primary carbon-carbon composite material to the impregnation liquid is 1:4.3.
[0128] Comparative Example 1
[0129] Based on Example 1, the changes are as follows:
[0130] The step of modifying the carbon nanotubes is omitted, and in the step of preparing the impregnation liquid matrix, the modified carbon nanotubes are replaced by carbon nanotubes without any treatment in equal amounts;
[0131] The rest of the operations are the same.
[0132] Comparative Example 2
[0133] Based on Example 1, the changes are as follows:
[0134] (1) In the step of preparing the hydrolyzed carbon-boron precursor, the boron doping step is omitted; in the hydrolysis step, the carbon-boron precursor is replaced with polyacrylonitrile in an equal amount;
[0135] (2) In the step of preparing modified carbon nanotubes, the modification step is omitted; in the step of preparing the impregnation liquid matrix, the modified carbon nanotubes are replaced with carboxylated carbon nanotubes in equal amounts;
[0136] (3) In the step of preparing the impregnation solution, N-(2-hydroxyethyl)ethylenediamine-N,N',N'-triacetic acid and palmitic acid components are replaced with an ethanol solution in equal amounts, wherein the mass concentration of the ethanol solution is 30%;
[0137] The rest of the operations are the same.
[0138] Performance Testing
[0139] (1) Wear resistance
[0140] The carbon-carbon composite materials prepared in Examples 1-3 and Comparative Examples 1-2 were tested for wear resistance, mechanical properties and corrosion resistance, respectively. The test results are as follows:
[0141]
[0142] The wear resistance was tested by the Zhongke Kaihua HT1000 friction and wear tester. The test conditions were as follows: the grinding time was 30 min, the grinding material was zirconium oxide, the friction radius was 3 mm, the motor frequency was 10 Hz, and the load was 15 N. The wear rate was calculated by the formula W = m / pFs, where W = wear rate (cm 3 .N -1 m -1 ), m-loss due to abrasion (g), p-actual density (gcm -3 ), F-load (N), S-friction travel (m), which can be calculated based on the friction radius;
[0143] High temperature resistance is the mass loss rate after high temperature treatment at 1000°C for 5.0h;
[0144] The method for testing the corrosion resistance is as follows: the carbon-carbon composite materials prepared in Examples 1-3 and Comparative Examples 1-2 are immersed in a 20wt% sodium chloride solution with a mass of 4 times, the immersion temperature is 40°C, the immersion time is 100 hours, and after the immersion, they are washed and dried, and then immersed in a 20wt% sodium carbonate solution with a mass of 4 times, the immersion temperature is 62°C, the immersion time is 100 hours, and after the immersion, they are washed and dried, and then the mechanical properties are tested.
[0145] The invention modifies the carbon nanotubes by firstly performing an acid treatment on the carbon nanotubes with an organic acid so that the surface of the carbon nanotubes contains more carboxyl groups, then performing an acyl chloride treatment, and then reacting with an amino group to complete the modification of the carbon nanotubes. The prepared modified carbon nanotubes have good dispersibility, and triethylamine and dopamine present a cross-linked stable structure on the surface of the carbon nanotubes, thereby enhancing the strength and stability of the carbon nanotubes. Polyacrylonitrile is used as a carbon source, and a composite of boric acid and polyacrylonitrile is used to make the matrix have better fluidity, increase the bonding strength of the interface, and at the same time boron can promote the graphitization of the carbon matrix. The impregnation liquid matrix presents a stable network structure, which is combined with N-(2-hydroxyethyl)ethylenediamine-N,N',N'-triacetic acid and palmitic acid components, so that the impregnation liquid has good homogeneity, good dispersibility and excellent bonding performance. In addition, the impregnation liquid contains more hydroxyl, carboxyl, amino and other groups, which improves the compatibility with carbon fiber, so that the carbon fiber cloth is fully and evenly compounded with the impregnation liquid. Under the joint action, the wear resistance and strength performance of the composite material are effectively enhanced, and the stability is improved.
[0146] In Comparative Example 1, the modification of carbon nanotubes is omitted, the dispersion force of carbon nanotubes is weak, and the aggregation is serious. The carbon nanotubes are directly used to prepare the impregnation liquid matrix, and the binding force between the carbon nanotubes and the hydrolyzed carbon-boron precursor is weak and unstable, which leads to the internal binding instability of the impregnation liquid matrix, further leading to the uneven composition of the impregnation liquid, serious agglomeration, and poor impregnation effect on the carbon fiber base cloth, which ultimately leads to poor strength performance, poor wear resistance, poor corrosion resistance and high temperature resistance of the prepared composite material, which greatly narrows the scope of use;
[0147] In Comparative Example 2, the doping of polyacrylonitrile with boric acid was omitted, the interface bonding strength between the matrix and the fiber was low, the graphitization degree of the carbon matrix could not be improved, the wear resistance was reduced, and the modification step was omitted in the step of preparing modified carbon nanotubes. The impregnation liquid matrix was directly prepared by compounding carboxylated carbon nanotubes and hydrolyzed carbon boron precursors. The bonding force between the two was not strong and the connection effect was weak for preparing the impregnation liquid. The omission of N-(2-hydroxyethyl)ethylenediamine-N,N',N'-triacetic acid and palmitic acid components would reduce the uniformity of the impregnation liquid, thereby reducing the impregnation effect on the carbon fiber cloth, thereby reducing the wear resistance and strength of the composite material to a certain extent, and the stability is not good.
[0148] Unless otherwise specified, all ratios and percentages described in the present invention are by mass ratios and percentages are by mass percentages.
[0149] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for improving the wear resistance of carbon-carbon composite materials by boron doping, characterized in that: The method comprises the steps of preparing a hydrolyzed carbon-boron precursor, preparing a modified carbon nanotube, preparing an impregnation liquid matrix, preparing an impregnation liquid, impregnation, carbonization, and densification; The preparation of the hydrolyzed carbon-boron precursor comprises the steps of boron doping and hydrolysis; The boron doping step comprises adding polyacrylonitrile to N,N-dimethylformamide, adding boric acid after stirring evenly, and performing ultrasonic treatment. After the ultrasonic treatment, the mixture is placed at 156-160° C. for heat treatment for 1.2-1.5 hours. After the heat treatment, the mixture is naturally cooled to room temperature to obtain a carbon-boron precursor. The preparation of modified carbon nanotubes includes pretreatment and modification steps; The pretreatment step comprises placing the carbon nanotubes in a sealed container, adding deionized water and sodium dodecyl sulfate and stirring, adding dihydroxymethylbutyric acid and tartaric acid after stirring evenly, raising the temperature to 83-89° C., stirring twice, filtering, washing, and drying after the stirring is completed to obtain carboxylated carbon nanotubes; The modification step comprises placing the carboxylated carbon nanotubes in a sealed container, adding thionyl chloride, raising the temperature to 108-113° C. for stirring reaction, and the reaction time is 18-22 hours. After the reaction is completed, filtering and drying are performed to obtain chlorinated carbon nanotubes; adding chlorinated carbon nanotubes to toluene, stirring evenly, adding triethylamine and dopamine, stirring evenly, raising the temperature to 100-105° C., and reflux reaction for 5.8-6.3 hours. After the reaction is completed, modified carbon nanotubes are obtained; The step of preparing the impregnation liquid matrix is as follows: placing the hydrolyzed carbon-boron precursor in dimethyl sulfoxide, stirring evenly, adding the modified carbon nanotubes to react, and after the reaction is completed, naturally cooling to room temperature, filtering, washing, and drying to obtain the impregnation liquid matrix; The step of preparing the impregnation liquid is to mix the impregnation liquid matrix with the ethanol solution, perform ultrasonic treatment, add N-(2-hydroxyethyl)ethylenediamine-N,N',N'-triacetic acid and palmitic acid after the ultrasonic treatment, stir, and obtain the impregnation liquid after the stirring.
2. The method for improving the wear resistance of carbon-carbon composite materials by boron doping according to claim 1, characterized in that: In the boron doping step, the ultrasonic treatment has an ultrasonic time of 30-35 min, an ultrasonic power of 342-357 W, and an ultrasonic frequency of 93-100 kHz; The mass ratio of the N,N-dimethylformamide, polyacrylonitrile and boric acid is 28-32:9-11:0.47-0.
53.
3. The method for improving the wear resistance of carbon-carbon composite materials by boron doping according to claim 1, characterized in that: The hydrolysis step comprises placing the carbon-boron precursor in a sodium hydroxide solution, raising the temperature to 92-97° C., stirring the solution at 200-215 rpm for 1.8-2.2 hours, and washing and drying the solution after the stirring reaction to obtain a hydrolyzed carbon-boron precursor. The mass concentration of the sodium hydroxide solution is 20-25%; The mass ratio of the carbon-boron precursor to the sodium hydroxide solution is 8.2-8.6:34-36.
4. The method for improving the wear resistance of carbon-carbon composite materials by boron doping according to claim 1, characterized in that: In the pretreatment step, the secondary stirring has a stirring speed of 547-572 rpm and a stirring time of 22-30 min; The drying is carried out at 76-80° C. for 2.8-3.3 hours; The mass ratio of the carbon nanotubes, deionized water, sodium dodecyl sulfate, dihydroxymethylbutyric acid and tartaric acid is 11.0-11.4:92-100:0.8-1.0:1.1-1.5:1.4-1.
7.
5. The method for improving the wear resistance of carbon-carbon composite materials by boron doping according to claim 1, characterized in that: In the modification step, the mass volume ratio of the carboxylated carbon nanotubes to thionyl chloride is 7.8-8.2 g:740-760 mL; The mass volume ratio of the toluene, acyl chloride carbon nanotubes, triethylamine and dopamine is 340-360 mL: 2.8-3.2 g: 0.6-0.8 g: 0.4-0.6 g.
6. The method for improving the wear resistance of carbon-carbon composite materials by boron doping according to claim 1, characterized in that: The step of preparing the impregnation liquid matrix is as follows: placing the hydrolyzed carbon-boron precursor in dimethyl sulfoxide, stirring evenly, adding the modified carbon nanotubes, and performing homogenization treatment. The homogenization time is 5-7 minutes, and the homogenization pressure is 4.0-4.5 MPa. After the homogenization treatment is completed, the temperature is increased to 76-80° C., and the reaction is carried out in a nitrogen atmosphere. The reaction time is 5.3-5.7 hours. After the reaction is completed, it is naturally cooled to room temperature, filtered, washed, and dried to obtain the impregnation liquid matrix; The mass volume ratio of the hydrolyzed carbon-boron precursor, dimethyl sulfoxide and modified carbon nanotubes is 8.3-8.7 g: 215-225 mL: 2.0-2.2 g.
7. The method for improving the wear resistance of carbon-carbon composite materials by boron doping according to claim 1, characterized in that: In the step of preparing the impregnation solution, the ultrasonic treatment has an ultrasonic time of 20-30 min, an ultrasonic power of 252-265 W, and an ultrasonic frequency of 35-40 kHz; The stirring temperature is 58-62°C and the stirring time is 30-40min; The mass concentration of the ethanol solution is 27-33%; The mass volume ratio of the impregnation liquid matrix, the ethanol solution, N-(2-hydroxyethyl)ethylenediamine-N,N',N'-triacetic acid and palmitic acid is 25.4-26.0 g: 48-52 mL: 0.8-1.2 g: 1.2-1.4 g.
8. The method for improving the wear resistance of carbon-carbon composite materials by boron doping according to claim 1, characterized in that: The impregnation step comprises arranging the carbon fibers in a sealed container, introducing an impregnation liquid, raising the temperature to 204-208° C., impregnating at 204-208° C. for 37-43 minutes, introducing argon gas after the impregnation, controlling the temperature to 204-208° C., raising the pressure to 3.0-3.5 MPa, maintaining the temperature and pressure for 2.7-3.3 hours, and obtaining a primary impregnated body after the temperature and pressure are maintained; The density of the carbon fiber cloth is 0.52-0.58 g / cm 3 , woven from 12K long fibers; The mass ratio of the carbon fiber cloth to the impregnating liquid is 1:3.0-3.
4.
9. The method for improving the wear resistance of carbon-carbon composite materials by boron doping according to claim 8, characterized in that: The carbonization step is to place the primary impregnated body in a carbonization furnace, carbonize it under an argon atmosphere, heat it to 740-760°C at a rate of 7.8-8.2°C / min, keep it warm for 35-45min, and after the heat preservation, heat it to 1240-1300°C at a rate of 4.5-5.5°C / min, keep it warm for 6.5-7.5h, and after the heat preservation, obtain a primary carbon-carbon composite material.
10. The method for improving the wear resistance of carbon-carbon composite materials by boron doping according to claim 9, characterized in that: The densification step comprises placing the primary carbon-carbon composite material in a sealed container, introducing an impregnation liquid, raising the temperature to 208-212° C., impregnating at 208-212° C. for 35-40 minutes, introducing argon gas after the impregnation, controlling the temperature to 208-212° C., raising the pressure to 3.8-4.2 MPa, maintaining the temperature and pressure for 3.3-3.7 hours, and obtaining a secondary impregnated body after the insulation and pressure maintenance; placing the secondary impregnated body in a carbonization furnace, Carbonization is carried out under an argon atmosphere, the temperature is increased to 600-640°C at a rate of 6.0-7.0°C / min, and the temperature is kept for 25-35 minutes. After the temperature is kept, the temperature is increased to 1300-1340°C at a rate of 3.7-4.3°C / min, and the temperature is kept for 6.2-6.8 hours. After the temperature is kept, the temperature is increased to 1860-1900°C at a rate of 3.0-3.5°C / min, and the temperature is kept for 2.2-2.8 hours to obtain a carbon-carbon composite material; The mass ratio of the primary carbon-carbon composite material to the impregnation liquid is 1:3.7-4.3.